The Social Stratification System in Forming a Balinese Identity - I Nyoman Yoga Segara,; Ravinjay Kuckreja, (Jurnal Kajian Bali (Journal of Bali Studies), 2024)
This article defines the various layers and identity labels of the Balinese society. Much of their indigenous customs have been linked with Hinduism, and many would regard the two to be inseparable. This article, however, attempts to separate the indigenous elements of ancestral worship from the Vedic or Hindu understanding of societal divisions in order to properly study the two and how they influence one another. The history of the island has enforced the rigid caste system, but the application of Hindu philosophy serves an idealized definition of caste. In such a way, the Hindu or Vedic belief does provide much relief for Balinese society. However, they are still defined by their patrilineal heritage, and are bound to ancestral worship as per their indigenous religion. Fueled by the contemporary socio-political landscape of Bali, there is a need to properly define what Balinese identity actually is.
Keywords: Bali; Balinese caste system; social stratification